A bibliometric analysis of climate change risk perception: Hot spots, trends and improvements - Fan, Jitong; Liu, Gang; Xia, Ziqian; Cai, Sanfa (Frontiers in Environmental Science, 2022)
Climate change is a global problem, and it is receiving increasing scientific attention due to its significant impact. To provide valuable insights for understanding and summarizing the research trends and prospects on climate change risk perception, this study takes a qualitative and quantitative analysis by using bibliometric tools. This analysis presents information related to authors, countries, institutions, journals, top cited publications, research hot spots, trends, and prospects. The analysis involved 4429 articles after rigorous screening and evaluated them on the risk perception of climate change in countries and the public. The majority of publications were published during the period of 2016–2022 (70.92%), with Climatic Change being the dominant journal and most research originating from the USA, England and Australia. The research content of this topic is primarily divided into several categories, including environmental sciences, atmospheric sciences, water resources and public health. The results showed that adaptation and vulnerability attract much attention. Finally, this paper identifies and discusses five research themes that should be further studied: determinants of perception, human behavior, human mental health risk, agriculture and adaptive strategy.